Intravesical Tumor-Selective Mucoadhesive Hydrogel for Effective Chemotherapy In Murine Model - Zheng B; Chen Z; Sun L; Quan J; Wei J; Huang B; Zhang D; Zhang P; Zhuo Y (International Journal of Nanomedicine)
Bin Zheng,1,2,* Zheng Chen,1,* Luping Sun,1,* Jing Quan,2 Jianwen Wei,1 Baoyuan Huang,1 Dahong Zhang,2 Pu Zhang,2 Yumin Zhuo1 1Department of Urology, The First Affiliated Hospital of Jinan University, Jinan University, Guangzhou, People’s Republic of China; 2Urology & Nephrology Center, Department of Urology, Zhejiang Provincial People’s Hospital (Affiliated People’s Hospital), Hangzhou Medical College, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Pu Zhang, Email zhangpuxjtuer@163.com Yumin Zhuo, Email tzhuoyumin@126.comIntroduction: The therapeutic efficacy of intravesical agents for bladder cancer (BCa) is frequently constrained by their clearance via urine flushing and periodic bladder emptying, as well as the absence of tumor-targeting capabilities. Consequently, an effective drug delivery system must possess both tumor-targeting and adhesion properties to overcome these limitations.Methods: In this study, we investigated a tumor-selective hydrogel as a potential vehicle for BCa treatment. For the first time in the field of intravesical therapy, we introduced the concept of pre-targeting, sequentially instilling modified polyarginine and membrane nanoparticles into the bladder to achieve selective gelation on the tumor surface. We comprehensively evaluated tumor selectivity, endocytosis pathways, organelle localization, and osmotic capacity, and demonstrated in vivo and in vitro degradation following drug delivery.Results: The pre-targeted hydrogel exhibited superior tumor selectivity. The drug-loaded membrane nanoparticles released during hydrogel degradation were internalized by tumor cells at levels exceeding those in normal cells by more than eightfold. Our findings indicated that this internalization process was energy-dependent and mediated by caveolin. Post-internalization, the drug-loaded membrane nanoparticles localized to the endoplasmic reticulum and Golgi apparatus, with minimal colocalization with lysosomes. Moreover, the hydrogel demonstrated profound penetration into tumor tissue. In terms of antitumor efficacy, the hydrogel loaded with gemcitabine exhibited significantly enhanced therapeutic effects compared to free gemcitabine.Conclusion: Our dual-functional hydrogel system exhibits robust anti-tumor activity against BCa, presenting a promising alternative for intravesical therapy. This innovative approach addresses key limitations of current treatments by combining tumor targeting with sustained drug adhesion, offering a novel strategy for the management of BCa.Keywords: intravesical therapy, pretargeted drug delivery, tumor-selective, hydrogel, mucoadhesive